La cura di sé come pratica educativa: le radici ellenistiche - Livia Romano (Firenze University Press, 2012)
The "self-care", yet one of the ethical principles of the hellenistic philosophies, is read again with a kind of disenchanted and post-modern view. Through a comparision between the Hellenistic and the modern ages, we can say that the first one is marked by the crisis of the pòlis, and the second one is living out the end of the national state with a sense of anxiety. So, by following Epicuro and the Stoicism, is possible to recognize in the practice of the "self-care" a pedagogic resource through which the Subject can activate a self-inquiry process able to involve or commit others human beings, planting the seeds for a planetary consciousness.